Pengaruh Biaya Operasional Terhadap Produktivitas Kerja di PD. Baratala Tuntung Pandang Tahun 2020-2021 - Noor Amelia; Gati Anjaswari; Mustaqim Mustaqim (Jurnal Ilmiah Akuntansi Keuangan dan Bisnis (JIKABI), 2023)
This study aims to determine the effect of operational costs on work productivity at PD. Baratala Tuntung Pandang in 2020-2021. The research method used is a quantitative research method with secondary data obtained from the company's quarterly profit and loss reports for 2020-2021. This research was conducted at the Baratala Tuntung Pandang Regional Company, one of the regional companies in Tanah Laut Regency. Data analysis techniques used quantitative data analysis through simple linear regression analysis, correlation coefficient analysis, and coefficient of determination analysis. The results of the correlation hypothesis test show that there is a very strong correlation between direct operational costs and work productivity with a correlation coefficient of 0.909 while the results of the indirect operational costs hypothesis test have no correlation with work productivity with a correlation coefficient of -696. Based on the results of the t test, it can be concluded that H0 is rejected and H1 is accepted, which means that operational costs directly affect work productivity in PD. Baratala Tuntung Pandang. This can be seen from the calculation of the t test where the t-count value is greater than the t-table value (5.340 2.571). In addition, direct operational costs also have a direct relationship with work productivity, so that if the value of operational costs increases, the value of work productivity will also increase.